Analysis of Global Positioning System-based attacks and a novel Global Positioning System spoofing detection/mitigation algorithm for unmanned aerial vehicle simulation. (May 2017) - Javaid, Ahmad Y; Jahan, Farha; Sun, Weiqing
Simulation test beds serve as a cost-effective and safe way to evaluate the system performance of various real world systems. With the rising concerns in the security of sensitive and critical systems, such as unmanned aerial vehicles (UAVs), a software simulation test bed is clearly the best choice given that the environment and various system components are modeled correctly. This becomes critical given the recently developed autonomous aerial vehicles. We therefore evaluate several available simulation test beds and use the most promising test bed to analyze the impact of Global Positioning System (GPS)-related attacks on navigation of UAVs. We also introduce a novel technique for GPS spoofing, attack detection, and mitigation. This paper presents GPS spoofing and GPS jamming attacks with their anatomy, design, and impact evaluation on navigation as well as a novel GPS spoofing mitigation and detection technique for UAVs, using UAVSim: an open source simulation test bed.